Kajian Fenimisme Dan Nilai-Nilai Pendidikan Dalam Novel Gadis Kretek Karya Ratih Kumala - Dwi Rahayu Saptiyakananta; Enggar Bunga Nareza Fiona; Natasya Dita Martshelia; Nisa’ul Fadhillah; Putri Dewi Afifah, Eni Nurhayati (Journal of Creative Student Research, 2023)
This article discusses the feminist movement (liberation) of women from the patriarchal movement that still exists today. The purpose of this article is to describe and explain the personalities of female characters, describe and explain the struggle for gender equality for female characters and apply educational values ​​in everyday life. Based on the results of the analysis, the results obtained are: 1) The personality of the female characters depicted through Roemaisa and Jeng Yah is a strong, independent and authoritative figure, while the character Purwanti is a character who dares to express her feelings in her youth, 2) The struggle for gender equality in this novel it is shown through the characters Roemaisa and Jeng Yah. These two women had a big influence on the cigarette business. 3) The educational values ​​in the Kretek Girl novel include: a) Religious values, which emphasize the relationship between humans and God, b) Moral educational values, related to the values ​​of good or bad human behavior, c ) Cultural educational values ​​related to the traditions and habits of society.